Comparative Proteomic Analysis of the Diatom Phaeodactylum tricornutum Reveals New Insights Into Intra- and Extra-Cellular Protein Contents of Its Oval, Fusiform, and Triradiate Morphotypes - Chuberre, Coralie; Chan, Philippe; Walet-Balieu, Marie-Laure; Thiébert, François; Burel, Carole; Hardouin, Julie; Gügi, Bruno; Bardor, Muriel (Frontiers in Plant Science, 2022)
Phaeodactylum tricornutum is an atypical diatom since it can display three main morphotypes: fusiform, triradiate, and oval. Such pleomorphism is possible thanks to an original metabolism, which is tightly regulated in order to acclimate to environmental conditions. Currently, studies dedicated to the comparison of each morphotype issued from one specific strain are scarce and little information is available regarding the physiological significance of this morphogenesis. In this study, we performed a comparative proteomic analysis of the three morphotypes from P. tricornutum. Cultures highly enriched in one dominant morphotype (fusiform, triradiate, or oval) of P. tricornutum Pt3 strain were used. Pairwise comparisons highlighted biological processes, which are up- and down-regulated in the oval (e.g., purine and cellular amino acid metabolism) and triradiate morphotypes (e.g., oxido-reduction and glycolytic processes) compared to the fusiform one used as a reference. Intersection analysis allowed us to identify the specific features of the oval morphotype. Results from this study confirmed previous transcriptomic RNA sequencing observation showing that the oval cells present a distinct metabolism with specific protein enrichment compared to fusiform and triradiate cells. Finally, the analysis of the secretome of each morphotype was also performed.